Formação tecnológica de formadores no mestrado profissional: mídias e multimodalidade - Mendes, Nilton (2019)
This research had as objective to critically investigate the use of different media and the multimodal work in a training context of trainers in a professional master program of a private university located in the city of São Paulo. From the perspective of Applied Linguistics (LA), the research sought to investigate how the process of technological training of media trainers is carried out and through them, in a collaboration between teacher, monitors and students, creating connections between classroom and on- line. For that, the work was based on the Socio-Historical-Cultural Activity Theory, the training of trainers and multimodality. This study is characterized as a Critical Collaboration Research (PCCol) for conceiving the transformation through the active and joint participation of those involved in the negotiation of meanings and meanings. The goal of PCCol is to know, observe and transform, in a critically-collaborative way, to enable possible interventions. In this study, the data were produced by means of filming and also from conversations originated during online classes in the WhatsApp application, in which the emphasis of the analysis lies. The discussion of the data allowed the understanding of the thematic content of the interactions of trainers of trainers and trainers in formation, analyzing the elements of the training activity, recognizing, through the speeches and lexical choices of the participants, marks of the use of varied media, multimodality and understanding about the topics. The results showed that the media contribute in the agility and the access, being able to increase the collaborative participation of the subjects and that the multimodality proposes different readings that open space for the discussion and production of the knowledge. However, the results also showed the need for greater mediation of online training space in the organization of shifts and interlacing of voices. This work reveals a deepening in the history of the technological formation of trainers with multiple media and multimodality, as well as points out possibilities for practices in online contexts